1991
DOI: 10.2165/00007256-199111050-00003
|View full text |Cite
|
Sign up to set email alerts
|

The ???Athletic Heart Syndrome???

Abstract: Cardiological findings in athletes are often similar to those observed in clinical cases. Electrocardiographic and cardiac imaging abnormalities as well as physical findings may be the same in both of these groups. Bradycardia and rhythm disturbances are the most common abnormalities in athletes. Most athletes with abnormal electrocardiograms are asymptomatic and numerous investigators have failed to detect heart disease in association with such electrocardiograms. In contrast to cardiac dysfunction observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 176 publications
0
48
0
Order By: Relevance
“…An increased left ventricular mass, associated with an increased internal diameter and wall thickness, is a commonly reported finding in the 'athlete's heart' (George et al 1991). The cardiac remodelling observed in athletes is associated with the specific haemodynamic requirements of the exercise undertaken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased left ventricular mass, associated with an increased internal diameter and wall thickness, is a commonly reported finding in the 'athlete's heart' (George et al 1991). The cardiac remodelling observed in athletes is associated with the specific haemodynamic requirements of the exercise undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Following the suggestion of differential cardiac remodelling in response to different types of physical training (Morganroth et al 1975), a large number of cross-sectional studies examining small numbers of athletes from a wide range of sports have been published, reviewed, and subjected to meta-analysis (George et al 1991;Pluim et al 1999). Whilst the majority of previous echocardiographic studies have examined small cohorts of athletes, a landmark paper examining 947 elite Italian athletes from 25 sports was published by Pelliccia et al (1991).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these health benefits are mediated by cardiovascular adaptations to a regular exercise program, such that physical exercise is an important component of many types of physical rehabilitation programs, including cardiac rehabilitation (recent examples in [5][6][7]). Regular exercise promotes a wide variety of cardiac adaptations, including in alterations in cardiac excitability [8,9], contractile force [10], stroke and end-diastolic volumes [11,12], and diastolic efficiency [13]. These physiological responses to regular exercise increase cardiac peak function, permitting higher levels of physical work [5,6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Sport-specific adaptations and differentiation of an athlete's heart were described 100 years ago (Morganroth et al, 1975;Landry et al, 1985;Hoogsteen et al, 2004). Several studies suggested that the precise alterations in cardiac structure associated with training may differ depending on the type of athletic activity (Pluim et al, 2000;Pelliccia et al, 1996;Landry et al, 1985;George et al, 1991;Pearson et al, 1986).…”
Section: Introductionmentioning
confidence: 99%